Faculty Associations Confront Accountability Governance in Ontario Universities - Webber, Michelle; Butovsky, Jonah (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
Much literature focusing on the academy is concerned with the spread of neo-liberalism into the university sector. We argue that universities in Canada are operating in an era of “accountability governance,” with ideologies, discourses, and practices centred on quality, accountability, and efficiency. We explore the interplay between accountability governance as a regime of power and the work of faculty associations, especially as they strive to preserve faculty members’ professional autonomy and control over their academic work. Using in-depth qualitative interviews with executive members of several Ontario university faculty associations, we explore themes of neo-liberalization and corporatization of the university, shrinking faculty budgets, program reviews, and strategic mandates. While opportunities for action and resistance for faculty unions arise, particularly at the level of senate, more militancy and radicalism are not favoured by many members, as political action is often seen as “unprofessional.”